Road Accessibility Analysis of Waling Municipality and Its Peripheral Settlements (Voice of Teacher, 2025)
This paper aims to investigate the concept of accessibility and how it can be incorporated in transport between urban and rural areas. Accessibility refers to people’s ability to reach goods, services and activities, which is the ultimate goal of transport activity. Accessibility can be evaluated from various perspectives including a particular group, mode, location or activity. Field data were collected from two different methods; one was the observation method and the other was interview method. The observation method was used for the collection of primary data in Waling. One of the main concerns of this study was to describe the accessibility analysis of urban center with periphery areas. The Interview method has been used for the access facilities survey. The interview was conducted on the basis of sample. Urban centers provide the access to goods and services for rural people with help of connecting paths, roads and other transport facilities to destinations and therefore activities (also called opportunities). Hence in this study accessibility refers the relative ease of reaching rural people to Waling urban center by use of the different mode of transport facilities for various purposes. This study has also explained in terms of travel time and cost and frequency of public transport service. The case of observed periphery because of the direct blacktopped and graveled road connection with Waling Urban center, therefore, villagers can easily transport agricultural products in the urban centers frequently. The study showed a significant role of transport services in the mobility of people between urban center and rural areas. The planner and policy makers should emphasis the purposed for the improvement of the transport network, however, has to be based on the anticipated growth of traffic volumes in the future which depend upon several factors like growth and distribution of population, location of industries and other socio-economic functions.